2022
DOI: 10.3390/molecules27196426
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Boron-Containing N-Substituted Oseltamivir Derivatives as Anti-Influenza A Virus Agents for Overcoming N1-H274Y Oseltamivir-Resistant

Abstract: To address drug resistance to influenza virus neuraminidase inhibitors (NAIs), a series of novel boron-containing N-substituted oseltamivir derivatives were designed and synthesized to target the 150-cavity of neuraminidase (NA). In NA inhibitory assays, it was found that most of the new compounds exhibited moderate inhibitory potency against the wild-type NAs. Among them, compound 2c bearing 4-(3-boronic acid benzyloxy)benzyl group displayed weaker or slightly improved activities against group-1 NAs (H1N1, H5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…[167] Other examples include CrO 3 -mediated oxidation of aromatic side chains, [22] MnO 2 -promoted dehydrogenative oxidation of β-aminoethane sulfonyl fluorides to corresponding ethylene derivatives, [168] Upjohn dihydroxylation, [169] sulfide to sulfoxide oxidation with NaIO 4 , [64] and alkylationoxidation sequence. [170] The SO 2 F fragment is also tolerant to various reductive agents, including NaBH 3 CN, [171] NaBH(OAc) 3 , [24,25,57] diphenyl disiloxane, [172] B 2 H 6 and borane complexes, [89,166,173] DIBAL, [57] sodium ditionite, [174] Bu 3 SnH, [175] Zn -HCl,, [176] Zn -HOAc, [157] Fe -HCl, [177] and Pd- [21,25,59,67,76,[177][178][179] or Ni- [180] catalyzed hydrogenation (Scheme 22).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[167] Other examples include CrO 3 -mediated oxidation of aromatic side chains, [22] MnO 2 -promoted dehydrogenative oxidation of β-aminoethane sulfonyl fluorides to corresponding ethylene derivatives, [168] Upjohn dihydroxylation, [169] sulfide to sulfoxide oxidation with NaIO 4 , [64] and alkylationoxidation sequence. [170] The SO 2 F fragment is also tolerant to various reductive agents, including NaBH 3 CN, [171] NaBH(OAc) 3 , [24,25,57] diphenyl disiloxane, [172] B 2 H 6 and borane complexes, [89,166,173] DIBAL, [57] sodium ditionite, [174] Bu 3 SnH, [175] Zn -HCl,, [176] Zn -HOAc, [157] Fe -HCl, [177] and Pd- [21,25,59,67,76,[177][178][179] or Ni- [180] catalyzed hydrogenation (Scheme 22).…”
Section: Methodsmentioning
confidence: 99%
“…The SO 2 F fragment is also tolerant to various reductive agents, including NaBH 3 CN, [171] NaBH(OAc) 3 , [24,25,57] diphenyl disiloxane, [172] B 2 H 6 and borane complexes, [89,166,173] DIBAL, [57] sodium ditionite, [174] Bu 3 SnH, [175] Zn – HCl,, [176] Zn – HOAc, [157] Fe – HCl, [177] and Pd‐ [21,25,59,67,76,177–179] or Ni‐ [180] catalyzed hydrogenation (Scheme 22).…”
Section: Chemoselective Reactions Of Functionalized Sulfonyl Fluoridesmentioning
confidence: 99%
“…2) mainly include M2 ion channel blockers: amantadine (1) and rimantadine (2), NA inhibitors: zanamivir (3), oseltamivir phosphate (4), peramivir (5) and laninamivir octanoate (6), and a PA inhibitor: baloxavir marboxil (7). [20][21][22] In the early stage, the existing antivirals have achieved remarkable results in the prevention and treatment of influenza. However, due to the highly error-prone properties of viral RdRp, drug-resistant viruses with reduced drug sensitivity emerge consistently, and their ability of human-tohuman transmission threatens again public health.…”
Section: Rsc Medicinal Chemistry Reviewmentioning
confidence: 99%
“…Molecular mechanism studies have found that 3061 (21) targeted the influenza NP with an IC 50 value of 0.1 μmol L −1 against reconstituted RdRp but led to resistance with the Y52H mutation on the NP (IC 50 > 30 μmol L −1 ). In addition, they found another compound, 367 (22), targeting PB1, which showed an inhibitory effect on RdRp enzymatic activity (IC 50 = 0.3-1 μmol L −1 ), and the mutant recombinant virus with H456P substitution in PB1 as well as the corresponding mutant protein expressed in the cell-based viral polymerase assay system had elevated resistance to 22 (IC 50 > 100 μmol L −1 ). In summary, the screening yielded two distinct classes of influenza virus inhibitors, thereby establishing a solid groundwork for the development of novel anti-influenza drugs.…”
Section: Np Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation